2019
DOI: 10.7150/jca.28364
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulated AKR1C2 is correlated with favorable prognosis in thyroid carcinoma

Abstract: Purpose : Aldo-keto reductase family 1, member C2 (AKR1C2) gene encodes for a member of the AKR superfamily and participates in the metabolism of various drugs. Moreover, tumor and normal tissues exhibit an evident difference in the expression level of this gene. Methods : We downloaded and analyzed AKR1C2 expression level and the data consisting of the clinicopathological features of 490 papillary thyroid carcinoma (PTC) tumor tissues and 59 normal thyroid tissues from The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…AKR1C2 expression is positively correlated with favorable tumor characteristics and prolongs survival time in primary breast cancer patients [ 34 ]. Elevated AKR1C2 expression also indicates a favorable prognostic and recurrence-free survival rate in papillary thyroid carcinoma [ 35 ]. Consistent with these studies, we identified that AKR1C2 is a tumor suppressor in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…AKR1C2 expression is positively correlated with favorable tumor characteristics and prolongs survival time in primary breast cancer patients [ 34 ]. Elevated AKR1C2 expression also indicates a favorable prognostic and recurrence-free survival rate in papillary thyroid carcinoma [ 35 ]. Consistent with these studies, we identified that AKR1C2 is a tumor suppressor in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a novel oncolytic agent targeting ICAM1 against bladder cancer is now in phase 1 of a clinical trial [38]. Additionally, DNAH3 was identified as novel predisposition gene using exome sequencing in a Tunisian family with multiple non-BRCA breast cancer instances [35].…”
Section: Resultsmentioning
confidence: 99%
“…There are fewer articles on the role of TSC22D3 in gastric cancer. The expression of AKR1C2 (Aldo-Keto Reductases Family 1 Member C2) has been associated with the prognosis of a variety of diseases including thyroid cancer, acute myeloid leukaemia (AML) and esophageal squamous cell carcinoma (ESCC) [23][24][25] . Some articles have now shown that the expression of AKR1C2 is associated with immunostimulants, immunosuppressants, chemokines and receptors, and that as a ferroptosisrelated gene, the high expression of AKR1C2 correlates with a good prognosis in GC, which could potentially serve as a promising prognostic biomarker for GC patients [26] .…”
Section: Discussionmentioning
confidence: 99%